Finding Worth in the Wilderness: The Abandonment of France and England's Earliest North American Colonies, 1534--1590 - Renaud, Tabitha (University of Ottawa (Canada), 2010)
The earliest attempts of France and England to colonize North America were disappointments. The sixteenth century saw French attempts to colonize the St. Lawrence Valley (1541-3) and Northern Florida (1562-5) and English attempts to colonize Roanoke Island (1585-7). In all three cases, the venture's hopes of finding valuable resources or the Northwest Passage were not realized and colonization was not achieved. This dissertation will examine four major types of difficulties the French and English faced in Canada, Virginia and Florida in the sixteenth century. They are challenges of environment and adaptation; internal conflicts such as rivalry and mutiny; challenges of Amerindian relations and, finally, challenges of transportation and communication. The struggles of these abandoned colonies will be compared with those of permanent colonies such as Jamestown, Quebec, Port Royal, Hispaniola and New Spain. Particular emphasis will be placed on the early struggles of Samuel de Champlain in Canada and John Smith in Virginia. It will be demonstrated that these were standard challenges of colonization for successful and unsuccessful colonies alike and that they could be overcome eventually with enough effort, experimentation, men and materials. France and England did not stop their earliest North American colonization projects because the task was too difficult. Rather, there appeared to be no worthwhile reason to waste resources or to battle rival powers such as Spain to hold these territories at this time.
Keywords: History, Canadian.; History, United States.; History, Modern.